PRESERVING CULTURAL IDENTITY AND INTERCULTURAL COMMUNICATION - Parmonova Mohigul Odiljon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Maintaining cultural identity and intercultural dialogue are among the important themes in the modern world. At a time when globalization processes are gaining momentum, different peoples and nations are trying to preserve their cultures, maintain their own unique traditions and Customs. At the same time, intercultural dialogue is an important tool in the development of mutual understanding, respect and cooperation between the peoples of the world. And finding a balance between maintaining cultural identity and intercultural dialogue is a complex but necessary process.